Relationships Between Traditional Chinese Medicine Constitution and Age-Related Cognitive Decline in Chinese Centenarians - Sun, Zhigao; Ping, Ping; Li, Yulong; Feng, Long; Liu, Fan; Zhao, Yali; Yao, Yao; Zhang, Pei; Fu, Shihui (Frontiers in Aging Neuroscience, 2022)
Background Age-related cognitive decline (ARCD) is a common condition among older adults, affecting 100 million people worldwide. Traditional Chinese Medicine’s (TCM) constitution is closely related to the occurrence and development of diseases in the elderly population. However, little is known about the relationships between TCM constitution and ARCD in the super-aged population. The present study aimed to investigate the relationships between the TCM constitution and ARCD in Chinese centenarians and to explore the application of the constitution to prevent ARCD in the elderly population. Methods Each participant underwent a standardized epidemiological investigation and physical examination, based on the China Hainan Centenarian Cohort Study. Data on the demographic characteristics and TCM constitution were collected using structured questionnaires. Results The present study included 636 centenarians aged 100–116 years. The prevalence of ARCD was 87.7% (n = 558 centenarians). In multiple linear regression analysis, an inverse relationship between Qi depression and Mini-Mental State Examination scales was significant after controlling for a wide range of other factors (P < 0.05). In multiple logistic regression analysis, Qi depression was positively associated with ARCD after full adjustment (P < 0.05). Conclusion As the first study in the world, the present study provides strong epidemiological evidence that Qi depression has a significant relationship with ARCD in Chinese centenarians, and regulating Qi depression may be a valuable method to prevent and treat ARCD in the elderly population.